MODEL PENINGKATAN IMPULSE BUYING MELALUI PHYSICAL SURROUNDING, SOCIAL SURROUNDING, DAN SALES PROMOTION - Siti Yuliana; Ken Sudarti (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2018)
This study attempts to know whether physical surrounding , social surrounding , and salespromotion impact on impulse buying , exhibit visitors held in citraland mall .Population in thisresearch is visitors exhibition .Samples to be taken as many as 100 respondents with using atechnique explanory sample , using multiple regression technique .This research result indicatesthat physical surrounding have a positive influence to sales promotion .Social surrounding havea positive influence to sales promotion .Physical surrounding have a positive influence to impulsebuying .Social surrounding have a positive influence to impulse buying .Sales promotion havea positive influence to impulse buyingKeywords : physical surrounding, social surrounding, sales promotion and impulse buying.